Bringing Cold War democracy to West Berlin : a shared German-American project, 1940-1972 - Krause, Scott H. (Routledge studies in modern European history, 2019)
"Within the span of a generation, Nazi Germany's former capital, Berlin, found a new role as a symbol of freedom and resilient democracy in the Cold War. This book unearths how this remarkable transformation derived from a network of liberal American occupation officials, and returned émigrés, or remigrés, of the Marxist Social Democratic Party (SPD). This network derived from lengthy physical and political journeys. After fleeing Hitler, German-speaking self-professed 'revolutionary socialists' emphasized 'anti-totalitarianism' in New Deal America and contributed to its intelligence apparatus. These experiences made these remigrés especially adept at cultural translation in postwar Berlin against Stalinism. This book provides a new explanation for the alignment of Germany's principal left-wing party with the Western camp. While the Cold War has traditionally been analyzed from the perspective of decision makers in Moscow or Washington, this study demonstrates the agency of hitherto marginalized on the conflict's first battlefield. Examining local political culture and social networks underscores how both Berliners and émigrés understood the East-West competition over the rubble that the Nazis left behind as a chance to reinvent themselves as democrats and cultural mediators, respectively. As this network popularized an anti-Communist, pro-Western Left, this book identifies how often ostracized émigrés made a crucial contribution to the Federal Republic of Germany's democratization"--